(untitled) (Research, Society and Development, 2020)
It presents an experimental activity built with low-cost materials during which the process of teaching and learning Physics was fostered to students in the public Basic Education network. In order to understand how low-cost experimental activities can make learning potentially significant in the study of Newton’s Laws, data were collected through pre- and post-teaching sequence questionnaires. Thus, it could be concluded that the activity enabled students to understand the issues addressed, and provided more interaction between teacher-student and pupil-student. Furthermore, it was found that the conciliation of the contextualized class with the experimental class resulted in significant learning, awakening the students’ interest in Physics.